Spectrum of Neurological Manifestations of HHV-6 Encephalitis in Immunocompetent Children – A Retrospective Study at a Tertiary Care Center in South India - Dona T Thomas; Kalpana Devadathan; Greeshma Baby; Mohammed PA Kunju; Prameela Joji (Annals of Indian Academy of Neurology)
Background: Human Herpes Virus 6 (HHV6) can cause severe neurological manifestations in immunocompromised individuals. However, there is sparse data regarding this in immunocompetent children. Objective: To describe the spectrum of neurological manifestations of HHV 6 infection and outcome in immunocompetent children admitted with suspected meningoencephalitis from January 2017 to December 2023. Methodology: We retrospectively analysed the electronic medical records of children admitted for suspected meningoencephalitis in a tertiary care Pediatric Neurology centre in South India. The children whose cerebrospinal fluid (CSF) was found to be positive for HHV6 DNA in film array meningoencephalitis (FA -ME) panel were included. Results: 204 /416 children with suspected meningoencephalitis were included in the study. HHV 6 was detected in 12 children. The median age was 19 months (Range – 6 months to 16 years). 4 (33%) of them were classified as febrile status. 5 (42%) children had meningoencephalitis, and one had aseptic meningitis. One child each had features of probable acute demyelinating encephalo myelitis (ADEM) and anti NMDA receptor encephalitis. 9 (75%) children had uneventful clinical recovery, one child died, one child with probable ADEM had extrapyramidal signs at discharge, which improved completely at one year follow up and the baby with autoimmune encephalitis had significant neurological deficits. Conclusion: HHV 6 can cause significant neurological problems, with significant morbidity and mortality in immunocompetent children also.